POST-PEACE: THE VICTORY OF INDIVIDUAL CANDIDATES AND POLICY PERFORMANCE IN PIDIE, ACEH - Darwin, Rizkika Lhena (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2022)
Electoral democracy has provided opportunities for candidates from individual path. Therefore, political parties do not become the single way to win the political election. This paper explores the victory of individual candidates in Pidie, Aceh, amid the difficulty of individual candidates winning against candidates from political parties which happened in other regions. This paper argues that the victory of individual candidates was strongly influenced by the risk of the policy performance of the ruling party in the previous period. The findings of this research are (1) individual candidates have no difference with political party’s candidate as they are not coming from social activist who bring alternative issues to the citizen. It only differs from its administrative requirements. (2) Pidie is an area where the majority of political parties support one candidate, so the presence of individual candidates becomes an alternative. (3) People's voting behavior in post-conflict areas tends to lead to rational choice, where past government policies become a consideration in voting in the next election. Thus, individual candidates in the context of regional elections will not affect the quality of democracy that takes place in Indonesia. Furthermore, in the positive side, people are increasingly maturing in politics because they make performance considerations the basis of their political choices. But the positive side is that people are increasingly maturing in politics because they make performance considerations the basis of their political choices. Strengthening the model of rational choice voting behavior will support the quality of elections and democracy that takes place in Indonesia.